Livehood Strategy As A Solution To Fulfilling Family Needs In Urban Slums - Firdaus W. Suhaeb; Ernawati S. Kaseng (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This study aims to find out how the concept of livelihood strategies and urban slums in a sociological perspective; and what forms a livelihood strategy on families in urban slums, as well as what impact of livehood strategy has on families in urban slums. The literature study method is used in this study, where from the secondary data obtained is then compiled so that later a conclusion can be drawn. The results of this study concluded that the livelihood strategies carried out by families in urban slums in order to meet their needs were carried out through double living patterns, livelihood source engineering, and spatial engineering (migration). The livelihood strategy is a way of adapting the head and family members to maintain the survival and economy of the family. The socio-economic impact of living strategies in meeting the needs of families in urban slums, namely in terms of education, housing, and income. So the family gets from the income of the various kinds of work they do. Therefore, the availability of adequate jobs from the government for families living in urban slums is highly expected.